Podcast sebagai Media Dakwah Baru di Kalangan Gen Z - Mufti Ali Abbas (Journal of Islamic Communication Studies, 2026)
The development of digital audio media has accelerated the transformation of da‘wah practices, rendering them increasingly adaptive to the characteristics and needs of Generation Z. In this context, podcasts have emerged as a new medium of da‘wah, offering dialogical, reflective, and contextual approaches. This study aims to analyze how podcasts frame da‘wah messages and shape Generation Z’s religious meaning-making within digital spaces. A qualitative approach grounded in the constructivist paradigm is employed to understand the construction of religious reality articulated through podcast narratives. The study applies the framing analysis model developed by Robert N. Entman, examining how da‘wah messages are structured through four framing devices: problem definition, causal diagnosis, moral evaluation, and treatment recommendation. Data were collected through content analysis of the podcasts Millennial Talks and Ngobrol Santai, complemented by in-depth interviews with ten Generation Z respondents. The findings indicate that podcasts frame da‘wah as an inclusive communicative practice that resonates with the lived experiences of Generation Z. They contribute to the formation of digital religious identity, position young audiences as active subjects of da‘wah, and provide a safe space for religious dialogue free from social pressure. The differing framing strategies Millennial Talks emphasizing educational dimensions and religious rationality, and Ngobrol Santai foregrounding personal experience and emotional closeness operate complementarily in strengthening the role of podcasts as contextual and adaptive digital da‘wah media within the contemporary landscape of Islamic communication.